PROVERBS AND SAYINGS AS A BASIC CONCEPT OF PAREMIOLOGY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article discusses issues such as paremiology and proverbs and aphorisms, which are its main units, the history of their creation, and their differences. As you know, paremiology studies ready-made, fixed phraseological units in the language. The history of the development of the science dates back to ancient history - the period of the development of Greek and Roman culture, we can find the definition of the first paremiological units in the works of Aristotle. In fact, the words of philosophers such as Socrates, Aristotle, Demosthenes, which have come down to us, appeared in those times and are recognized as the first aphorisms. Russian linguists who created after Aristotle consider proverbs as a phraseological unit. For this reason, proverbs can be studied from two different angles, we approached proverbs as a paremiological tool.